The sedge Carex secalina – critically endangered species in Poland: new locality in the breeding colony of black-headed gull Chroicocephalus ridibundus - Sandecki, Rafał (Biodiversity: Research and Conservation, 2016)
A new locality of rye sedge Carex secalina, a critically endangered species was discovered on an island of Lake Kusowo, in the vicinity of Bydgoszcz (Kuyavian-Pomeranian Province), in June 2015. The species was found in a breeding colony of black-headed gull Chroicocephalus ridibundus. The population size was estimated at least at 30 individuals and all of them produced generative shoots. This locality of C. secalina is the northernmost in Poland and the only ascertained, apart from Inowrocław Plain. Colonization of the island by C. secalina was caused, probably, by zoochory as a result of accidental bringing of propagules by gulls, together with nesting material from outside the colony.